Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.14245/ns.1836102.051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Inpatient and Outpatient Preoperative Factors and Postoperative Outcomes in 2-Level Cervical Disc Arthroplasty

Abstract: ObjectiveThe purpose of this study was to evaluate factors associated with inpatient admission following 2-level cervical disc arthroplasty (CDA). A secondary aim was to compare outcomes between those treated on an inpatient versus outpatient basis. MethodsUsing data from the American College of Surgeons National Surgical Quality Improvement Program database, multivariate logistic regression analysis was used to assess the independent effect of each variable on inpatient or outpatient selection for surgery. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…1,2 With continued improvements in technology and devices, recent studies have demonstrated excellent medium-to longterm outcomes following CDR in properly selected patients. [3][4][5][6][7][8] Compared to ACDF especially, CDR has shown equally if not more superior outcomes in various measures: PROMs, patient satisfaction, rate of postoperative dysphagia, rate of revision surgeries or secondary surgeries, adjacent segment degeneration, and cost-effectiveness. [9][10][11][12][13][14][15][16][17][18] It is currently accepted that maintaining or increasing cervical lordosis is an important goal in the surgical treatment of cervical spondylotic myeloradiculopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 With continued improvements in technology and devices, recent studies have demonstrated excellent medium-to longterm outcomes following CDR in properly selected patients. [3][4][5][6][7][8] Compared to ACDF especially, CDR has shown equally if not more superior outcomes in various measures: PROMs, patient satisfaction, rate of postoperative dysphagia, rate of revision surgeries or secondary surgeries, adjacent segment degeneration, and cost-effectiveness. [9][10][11][12][13][14][15][16][17][18] It is currently accepted that maintaining or increasing cervical lordosis is an important goal in the surgical treatment of cervical spondylotic myeloradiculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical disc replacement (CDR) has been established as a safe and effective surgical option for patients with degenerative disc disease who fail nonoperative management, [1][2][3][4][5][6][7][8] with numerous studies demonstrating similar or superior outcomes in various measures, including adjacent segment pathology, patientreported outcome measures (PROMs), rate of dysphagia, patient satisfaction, rate of revision and secondary surgeries, and cost-effectiveness compared to anterior cervical discectomy and fusion (ACDF). [9][10][11][12][13][14][15][16][17][18] Although the clinical benefits of CDR have been well-established in literature, the use of this technique in patients with nonlordotic cervical sagittal alignment is not well-established.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to decrease the risk of ASD in cervical surgery, cervical disc arthroplasty (CDA) was introduced as an alternative treatment for cervical disc degenerative diseases (CDDDs) in the past 20 years [5]. With a mobile device between two contiguous vertebrae, the mobility of operated segments can be preserved, which may potentially decrease the incidence of ASD postoperatively [6]. Moreover, CDA was reported to show better improvement in clinical functions than fusion surgery because the normal kinematics of the involved segments are maintained [7].…”
Section: Introductionmentioning
confidence: 99%
“…The number of outpatient CDR procedures shows an increasing trend in recent years. [ 19 ] Several studies have reported the noninferiority of outpatient CDR compared with outpatient ACDF or inpatient CDR. [ 19 27 ] However, the generalizability of these studies is limited by the retrospective study design, small sample size, and low incidence of CDR-associated complications.…”
Section: Introductionmentioning
confidence: 99%